Clathrin-mediated trafficking and PIN trafficking are required for auxin canalization and vascular tissue formation in Arabidopsis - Mazur, Ewa; Gallei, Michelle; Adamowski, Maciek; Han, Huibin; Robert, Hélène S; Friml, Jiří (Plant science, 2020)
The flexible development of plants is characterized by a high capacity for post-embryonic organ formation and tissue regeneration, processes, which require tightly regulated intercellular communication and coordinated tissue (re-)polarization. The phytohormone auxin, the main driver for these processes, is able to establish polarized auxin transport channels, which are characterized by the expression and polar, subcellular localization of the PIN1 auxin transport proteins. These channels are demarcating the position of future vascular strands necessary for organ formation and tissue regeneration. Major progress has been made in the last years to understand how PINs can change their polarity in different contexts and thus guide auxin flow through the plant. However, it still remains elusive how auxin mediates the establishment of auxin conducting channels and the formation of vascular tissue and which cellular processes are involved. By the means of sophisticated regeneration experiments combined with local auxin applications in Arabidopsis thaliana inflorescence stems we show that (i) PIN subcellular dynamics, (ii) PIN internalization by clathrin-mediated trafficking and (iii) an intact actin cytoskeleton required for post-endocytic trafficking are indispensable for auxin channel formation, de novo vascular formation and vascular regeneration after wounding. These observations provide novel insights into cellular mechanism of coordinated tissue polarization during auxin canalization.
Keywords: proteiny huseníčku; Endocytosis; Actins; Arabidopsis; PIN1; polarita buněk; Endocytic trafficking; membránové transportní proteiny; Auxin canalization; regulátory růstu rostlin; Arabidopsis Proteins; Clathrin; kyseliny indoloctové; Clathrin-mediated trafficking; aktiny; endocytóza; Membrane Transport Proteins; klathrin; biologický transport; Cell Polarity; Indoleacetic Acids; Plant Growth Regulators; Cell polarity; Protein Transport; Auxin; transport proteinů; Biological Transport